Hormone Receptors in Breast Cancer - Fuqua, Suzanne A. W. (Cancer Treatment and Research, 2009)
This book provides an up-to-date resource of the role of hormone receptors in breast cancer written in depth for both the basic molecular academic researcher and translational scientist. Advances in basic science of molecular endocrinology have undoubtedly been translated into clinical practice, and clinicians caring for this disease need to be knowledgeable about these developments. The molecular basis of hormone action has been elucidated, and the relative significance of the different estrogen and progesterone receptor isoforms has been explored. This explosion of information has led to exciting new areas of gene specific targeting of the disease, and breast cancer prevention. Paradigm shifts in treatment options and sequencing have recently occurred in breast cancer management, necessitating close cooperation and communication between translational scientists and physicians. Hormone Receptors in Breast Cancer focuses on providing this communication. "Hormones play an essential role in both the development of breast cancer and its therapy. This text provides a comprehensive review of the key receptors and signaling pathways that effect breast cancer growth leading figures in the field provide insight into the basic biology and clinical issues relevant to this devastating disease." Steven T. Rosen, MD, Series Editor.